Investigating the internal structure of the Antarctic ice sheet: the utility of isochrones for spatiotemporal ice-sheet model calibration - Sutter, Johannes; Fischer, Hubertus; Eisen, Olaf (The Cryosphere, 2021)
Ice-sheet models are a powerful tool to project the evolution of the Greenland and Antarctic ice sheets and thus their future contribution to global sea-level changes. Testing the ability of ice-sheet models to reproduce the ongoing and past evolution of the ice cover in Greenland and Antarctica is a fundamental part of every modelling effort. However, benchmarking ice-sheet model results against real-world observations is a non-trivial process as observational data come with spatiotemporal gaps in coverage. Here, we present a new approach to assess the accuracy of ice-sheet models which makes use of the internal layering of the Antarctic ice sheet. We calculate isochrone elevations from simulated Antarctic geometries and velocities via passive Lagrangian tracers, highlighting that a good fit of the model to two-dimensional datasets such as surface velocity and ice thickness does not guarantee a good match against the 3D architecture of the ice sheet and thus correct evolution over time. We show that palaeoclimate forcing schemes derived from ice-core records and climate models commonly used to drive ice-sheet models work well to constrain the 3D structure of ice flow and age in the interior of the East Antarctic ice sheet and especially along ice divides but fail towards the ice-sheet margin. The comparison to isochronal horizons attempted here reveals that simple heuristics of basal drag can lead to an overestimation of the vertical interior ice-sheet flow especially over subglacial basins. Our model observation intercomparison approach opens a new avenue for the improvement and tuning of current ice-sheet models via a more rigid constraint on model parameterisations and climate forcing, which will benefit model-based estimates of future and past ice-sheet changes.